State-of-the-art anesthesia practices: a comprehensive review on optimizing patient safety and recovery - Guolu Fu; Lili Xu; Huaqing Chen; Jinping Lin (BMC Surgery)
Abstract Objective This review explores recent advancements in anesthesia care, focusing on the integration of innovative practices to enhance patient outcomes across the perioperative period. Methods Following the framework of Whitmore and Knafl, we systematically searched six databases (PubMed, Google Scholar, EMBASE, CINAHL, OVID, and Cochrane Library) for studies published from January 2020 to January 2024, relating to advancements in anesthesia care, best practice implementation, and patient outcomes. After independent screening and data extraction by two reviewers, the review focuses on innovations in anesthetic drugs, monitoring technologies, anesthesia techniques, and evidence-based practices in anesthesia and clinical guidelines. Results Of the 25,984 studies retrieved, 26 met inclusion criteria. Recent developments in anesthetic drugs have improved safety and efficacy, reducing complications. Advanced monitoring devices, such as multiparameter and brain function monitors, have enhanced patient safety through real-time assessments. Innovations in regional anesthesia and ultrasound-guided nerve blocks have led to better pain management, reduced recovery time, and minimized morbidity. Additionally, evidence-based practices like comprehensive preoperative assessment, patient education, and multidisciplinary teamwork significantly improved patient outcomes. Conclusion Integrating the latest innovations and best practices in anesthesia care is essential for optimizing patient outcomes. Ongoing research and adoption of advanced technologies are crucial to addressing current challenges and enhancing anesthesia quality. This review emphasizes the importance of a holistic approach from preoperative preparation to postoperative recovery to achieve optimal patient outcomes.